Особливості народжуваності у жінок середнього віку - Аксьонова, С.Ю. (Інститут демографії та соціальних досліджень НАН України, 2009)
У статті на основі фактичного матеріалу розглянуто особливості народжуваності дітей жінками середнього віку. Доведено, що стрімкі темпи підвищення дітородної активності у жінок зрілого віку, які спостерігаються протягом останніх років, обумовлюються нашаруванням процесу реалізації відкладених народжень на поширення демографічної тенденції «постаріння» материнства. Внесок жінок 35–39 років у сумарний показник народжуваності за період 1997–2008 рр. збільшився у 2 рази. В статье на основе фактического материала рассмотрены особенности рождаемости детей женщинами среднего возраста. Доказано, что стремительные темпы повышения детородной активности у женщин зрелого возраста, которые наблюдаются на протяжении последних лет, обуславливаются наслоением процесса реализации отложенных рождений
на распространение демографической тенденции «постарения» материнства. Вклад женщин 35–39 лет в суммарный показатель рождаемости за период 1997–2008 гг. увеличился в 2 раза. In Ukraine in 2008 childbearing activity of women aged 35 to 39 was more than twice higher as to its level in 2001. As a result, in 2008 age-specific fertility rate for women aged 35 to 39 was
19.7 per 1,000 women, compared with 9 in 2001. During 2001–2008 their contribution to the total fertility rate was significantly increased also. In the context of different wants competition
the advanced fertility level of women aged 35 to 39 can be seen as recognition of the true value of children for generation, which represent these women. Their fertility rose mainly due to the
second parity births. The percentage of the first parity children born by women aged 35 and older, does not exceed 1.8% of all first-borns in Ukraine. In the view of increasing of the mean age of mother at birth the process of the concentration of births in age women groups after 35 will be enlarged. It challenges health care sphere to improve quality of medical services, particularly
in the reproductive area. This level is significantly lower than the level in the most of European countries. In the distribution of children by birth order for 35–39-year-olds mothers the second
parity children are twice as much as first-borns and triply more than third parity. This fact and special socio-demographic sample survey of population in childbearing age in Ukraine “Family
and Children, 2008”, show the strengthening of the reproductive attitudes towards two-child family model.